THE ECONOMIC MODERNIZATION OF UZBEKISTAN (ResearchJet Journal of Analysis and Inventions, 2021)
In this article all states are facing financial challenges induced by the pandemic, but states that have taken steps to modernize their tax codes—and minimize the economic impact of the taxes they do levy—can be expected to recover more quickly than states that have unduly burdensome tax structures.